Induction of Abortion by Prostaglandins E1 and E2. Issue 5704 (2nd May 1970) - Embrey, M. P.
Abstract : Intravenous infusions of prostaglandin E (E1 or E2 ) were used for termination of pregnancy in 11 patients. Induction of abortion was successful in nine instances and in eight the abortion was complete. No undesirable side-effects were recorded.